Sustainability status of mangrove rehabilitation in Natuna Regency, Indonesia: A rapid appraisal using RAPFISH - Metananda, Arya A.; Al-Reza, Dimaz D.; Hanum, Cut M.; Afrianto, Whisnu F. (Narra Sains Indonesia, 2025)
Mangrove rehabilitation success is determined not only by biophysical recovery but also by social engagement, economic viability, and institutional governance. However, sustainability constraints in locally managed rehabilitation sites remain insufficiently characterized. The aim of this study was to evaluate the sustainability status of mangrove rehabilitation in Bandarsyah Village, Natuna Regency, Indonesia, and to identify key leverage attributes across ecological, social, economic, and institutional dimensions. A Rapid Appraisal for Fisheries approach using Multidimensional Scaling (RAPFISH–MDS) was applied across four sustainability dimensions. Data were derived from structured field observations, document review, and semi-structured interviews with key stakeholders, including local government officers, rehabilitation practitioners, and community representatives. Sustainability attributes were scored using a standardized rubric and analyzed using MDS. Leverage analysis identified sensitive attributes influencing sustainability, while Monte Carlo simulation assessed the robustness of ordination results. The findings revealed that the ecological (MDS score 72.02) and social (72.52) dimensions were classified as sustainable, suggesting favorable environmental conditions and relatively strong community engagement. In contrast, the economic (MDS score 49.79) and institutional (34.75) dimensions were less sustainable, indicating limited livelihood benefits, weak financing continuity, and constrained governance capacity. Leverage analysis identified mangrove density, community access, rehabilitation funding, and policies and planning as the most influential attributes. Monte Carlo analysis confirmed the stability of the ordination, with small deviations from MDS scores (2.52–4.24), low stress values (0.10–0.11), and high model fit (R2=0.99). While mangrove rehabilitation in Bandarsyah Village is supported by ecological resilience and social participation, long-term sustainability is constrained by economic and institutional weaknesses. Strengthening financing mechanisms, operationalizing site-level planning, and improving governance enforcement are critical to sustaining rehabilitation outcomes in Natuna Regency.